Socio-economic reason to save an international wetland - Kaffashi, Sara; Shamsudin, Mad Nasir; Radam, Alias; Abdul Rahim, Khalid (Taylor & Francis, 2015)
A contingent valuation study was conducted to investigate the values of Shadegan International Wetland to the non-current users of this ecosystem. Structural equation modelling (SEM) was employed to model the effect of respondents attitudinal and sociodemographic characteristics on their willingness to pay (WTP). Results showed that respondents’ concerns on wetland management, income and education had direct effect on their WTP. Results of non-parametric and binary logit models to estimate WTP showed that respondents were willing to donate US$2.75 and US$3.18 per household per month, respectively. Simulation of results for future scenarios showed that only if income increment would be more than price increase, the market share of better conservation scenarios of wetland will increase. Estimated benefit was compared with opportunity cost of the wetland for other land uses. The results concluded that regardless of enormous benefits of wetland in limitless time, the current benefit of preservation wetland is economically valuable.